Examination of Surgically Important Healthy Life Expectancy and Respiratory Tract Deaths: The Relationship between Tuberculosis-Related Deaths and Health Adjusted Life Expectancy (HALE) - ÖZSAN, Dr. İsmail (International Journal of Innovative Research in Medical Science, 2022)
Background: The aim of the research is to evaluate the relationship between surgically important healthy life expectancy and respiratory tract deaths on the relationship between tuberculosis-related deaths and Health Adjusted Life Expectancy (HALE). Methods: ICD-10 (International Classification of Diseases 10th Revision) mortality and HALE data of WHO were used. In ICD-10 mortality data, a total of 12 countries have been reported tuberculosis caused deaths from 1996 to 2017. In total, 7 countries had sufficient data for panel data analyze from 2000 to 2011. Results: Tuberculosis caused female, male and total deaths were negatively correlated with HALE at birth and HALE at 60 ages (p<0.01). HALE at birth and HALE at 60 ages did not have significant contribution to tuberculosis related deaths for both genders and in total (p>0.05). Fixed, random or time fixed models did not explain effects of HALE on tuberculosis related deaths. Conclusion: Mortality of tuberculosis is more common in males, and in respiratory related TB. It is suggested to examine the effects of diseases that decrease life expectancy specifically on HALE. In this regard, the research may lead to studies examining the relationship between other mortality-related diseases and HALE in Public Health Perspective.